Evaluation of physical and psychological differences for age, gender and discipline in elite gymnasts in Iceland - Sandra Dögg Árnadóttir 1976- (2021)
The objectives of the present study were: (1) to evaluate the difference in anthropometry, body composition, and physical fitness concerning age, gender, and discipline; (2) to evaluate the difference in psychological skills in terms of age, gender, and discipline; and (3) to identify the impact that the competition period had on physical measurements of elite gymnasts in Iceland. Methods: Eighty-six gymnasts from three gymnastics disciplines; Women’s artistic gymnastics, Men’s artistic gymnastics and TeamGym, participated in the study. The physical tests were: The Men‘s Gymnastics Functional Measurement Tool and The Gymnastics Functional Measurement Tool. Three questionnaires were on offer: the Test of Performance Strategies Questionnaire, the Sport Mental Toughness Questionnaire, and the Sport Anxiety Scale–2 Questionnaire. The Independent samples t-test was used to compare groups and the Paired samples t-test to compare pre-and post-measurements. Physical results: Seniors scored higher than juniors in all except push-ups. Males had more strength than females, who had more flexibility. Artistic gymnasts had more hanging strength and flexibility than TeamGym, who had more grip strength and speed. Psychological results: seniors had more activation than juniors, who had more imagery. Females used more self-talk in practice than men and TeamGym showed more emotional control in practice than Artistic. Male showed more control than females, who showed more worry and concentration disruption. Juniors show more concentration disruption than seniors. Post-competition period flexibility and balance was less than pre-competition. Conclusion: Maintaining physical abilities during competition period and training psychological skills might benefit elite Icelandic gymnasts. Keywords: Icelandic gymnastics, Artistic gymnastics, TeamGym, Physical test, psychological skills. Markmið þessarar rannsóknar var að: (1) meta mun á líkamssamsetningu og líkamlegum þáttum eftir aldri, kyni og grein; (2) meta mun á sálfræðilegum þáttum ...